Gossip as Practice, Gossip as Care: Affective Information Practices in the Archives - Guerrero, Emily (Archivaria, 2022)
Often seen as suspect and untrustworthy, gossip as it is currently conceptualized comes from historic attempts by people who have experienced social marginalization to share information, build stronger relationships, and assess a dominant narrative against lived experience. In this article, I will be outlining how gossip has animated my archival work at the Crista Dahl Media Library and Archives, an artist-run centre in Vancouver, BC, and using the Crista Dahl Media Library and Archives as a case study. Several distinct uses of gossip emerge: these include offering space for archives workers to connect and build solidarity, opening up new avenues for reassessing what we consider to be relevant information in archival description, providing strategies for navigating sensitive information within collections, and acting as an alternative to narratives of trauma when considering archival silences. Drawing on practice theory and studies of community archives and deeply influenced by an ethos of transformative justice, this project is connected to the growing body of scholarly work that examines information and memory work through the lens of affect theory and a feminist ethics of care. This work contributes to the articulation of person-centred archival praxis by theorizing gossip as a tactic of care that trains the ear to better notice the experiences, complaints, and contributions of the people surrounding the records at hand.